2020
DOI: 10.1111/tbj.13986
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcome, postoperative complications, and mammographic changes after intraoperative radiotherapy with electrons (IOERT) as a boost in a large single‐institution cohort of breast cancer patients

Abstract: Advantages of using intraoperative radiotherapy with electrons (IOERT) as a boosting modality in breast‐conserving therapy include the direct visualization of the tumor bed, a reduced skin dose, and patient convenience. We report oncological outcome, postoperative complication rate, and mammographic changes on follow‐up imaging in women treated at our institution with IOERT as a boost modality in breast‐conserving therapy for early‐stage breast carcinoma. Between January 2007 and June 2018, 763 consecutive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Conventionally fractionated WBI (50 Gy in 5 weeks) combined with IORT photon boost was shown to be a standard alternative to other boost techniques [ 29 ]. Moderate hypofractionation WBI (40.05 Gy in 3 weeks) combined with an IORT boost has been confirmed to be safe and feasible using both electrons [ 30 , 31 , 32 , 33 ] and photons [ 15 , 16 , 34 , 35 ]. Our pioneering experience has shown that the combination of immediate IORT plus moderate HWBI is accompanied by favorable results in relation to chronic toxicity and aesthetic results, both in patients with early and locally advanced disease [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally fractionated WBI (50 Gy in 5 weeks) combined with IORT photon boost was shown to be a standard alternative to other boost techniques [ 29 ]. Moderate hypofractionation WBI (40.05 Gy in 3 weeks) combined with an IORT boost has been confirmed to be safe and feasible using both electrons [ 30 , 31 , 32 , 33 ] and photons [ 15 , 16 , 34 , 35 ]. Our pioneering experience has shown that the combination of immediate IORT plus moderate HWBI is accompanied by favorable results in relation to chronic toxicity and aesthetic results, both in patients with early and locally advanced disease [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, IORT boost is an excellent treatment when using moderate hypofractionation radiotherapy and is therefore worthy of being combined with an ultrafractionation WBI protocol that produces similar toxicity figures to the moderate hypofractionation protocols [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few articles in the literature about imaging findings in patients treated with IORT. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Most of these studies are more than 10 years old and have been performed by a few groups involved in the early clinical trials comparing IORT and WBRT. A limited number of findings have been evaluated, and conflicting results were reported.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few reports on the radiological findings in patients treated with IORT. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Some of them have reported that postoperative changes in mammography and ultrasound (US) are more pronounced in patients treated with IORT compared with those treated conventionally with WBRT. 7 , 8 , 9 , 11 , 13 However, radiological findings, especially sonographic results, after IORT are not well documented.…”
mentioning
confidence: 99%
“…Many single-arm studies have demonstrated the efficacy and safety of IORT boost+WBI; [33][34][35][36][37][38][39][40][41][42][43] however, comparative studies on IORT boost+WBI and conventional radiotherapy are still lacking. Through a search of major databases, we screened nine comparative studies of IORT boost+WBI versus conventional radiotherapy, with varying results.…”
Section: Discussionmentioning
confidence: 99%